Efeito da aplicação de um protocolo de fadiga nas variáveis cinemáticas e eletromiográficas de sujeitos após a reconstrução do ligamento cruzado anterior - Lessi, Giovanna Camparis (2015)
The incidence of anterior cruciate ligament (ACL) injury in female athletes is higher compared to men in the same sports activity. Subjects who have undergone ACL reconstruction show biomechanical changes that may predispose to a second injury. In addition, the muscular fatigue can increase the ACL injury risk. However, few studies have evaluated the effects of muscular fatigue in the kinematics and muscle activation in patients with ACL reconstruction, and no studies had compared the effects between men and women who undergoing reconstruction. Thus, the aim of this thesis was to evaluate the effects of muscular fatigue on the trunk, pelvis and lower limb kinematics, as well as the lower limb muscle activation during single-leg landing between two distinct groups of subjects, healthy recreational athletes and patients who have undergone ACL reconstruction. We also aim to compare the differences of the effects of fatigue between healthy men and women, and between men and women with ACL reconstruction. This thesis is divided into three studies, in which were performed kinematic analysis of the trunk, pelvis, hip and knee and electromyography of the gluteus maximus, gluteus medius, vastus lateralis and biceps femoris, during a singleleg landing, before and after a fatigue protocol. The first study compared healthy female and male recreational athletes; the second study compared recreational athletes with ACL reconstruction to a healthy control group, and the third study compared men and women with ACL reconstruction. The first study showed that fatigue caused changes in knee kinematics that could predispose healthy women to ACL injury. The second study found that fatigue can alter the kinematics and muscle activation, but these changes were not different between healthy subjects and patients who have undergoing ACL reconstruction. Finally, the third study showed that fatigue leads to kinematic changes that may predispose women who underwent ACL reconstruction to a second injury.